Robustly Repeatable, Permeable, and Multi‐Axially Stretchable, Adhesive Bioelectronics With Super‐adaptive Conductive Suction Cups for Continuously Deformable Biosurfaces - Gyun Ro Kang; Gui Won Hwang; Dohyun Lim; Seung Hwan Jeon; Minwoo Song; Chan‐Hwa Hong; Hye Jin Kim; Changhyun Pang (Advanced Science)
Abstract Skin‐integrated wearable bioelectronics offer immense potential for continuous health monitoring, diagnosis, and personalized therapy. However, robustly repeatable and permeable adhesive interfaces with omnidirectional stretchability for adaptability to continuously deforming skin surface remain a critical challenge and often results in issues such as delamination, void, and signal degradation. This study presents a highly adaptable bioelectronic device with a repeatable, robust and biocompatible adhesive interfaces designed for dynamic wet skin surfaces. The device integrates a conductive softened‐double‐layered octopus‐inspired nanocomposites adhesive and kirigami metastructure (cs‐OIA_k). The cs‐OIA_k achieves skin‐like softness, electrical stability (ΔR/R0 < 10, under 10 000 cycles) and omnidirectional stretchability (a maximum of 200%) to accommodate skin deformation. Additionally, the hierarchical structural design of cs‐OIA_k enables repeatable robust adhesion (> 10 000 cycles) and vertical alignment to ensure reversible adhesion against dynamically deforming surface (−30% to 100%, depending on skin thickness, site, and age) without skin irritation. Based on these characteristics, the highly adaptable skin‐adhesive bioelectronics are demonstrated to achieve reliable electrocardiogram (ECG) and electromyogram (EMG) signal measurements even under shoulder movements with extreme skin deformation. This approach utilizing multi‐axially stretchable, repeatable robust adhesives, permeable and biocompatible bioelectronics provides new insights for the development of advanced wearable systems and human–machine interfaces.